PENGARUH GAYA KEPEMIMPINAN DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PT. WAHANA OTTOMITRA MULTIARTHA FINANCE - Bagus Hadiyanto Widodo; Pusporini Palupi Jamaludin (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
This study aims to determine the Influence of Leadership Style and Work Discipline on Employee Performance at PT. Wahana Ottomitra Multiartha Finance in South Tangerang, both partially and simultaneously. This type of research uses a descriptive quantitative method. The sampling technique uses a saturated sample of 62 respondents. Data analysis techniques use data instrument tests, classical assumption tests, regression analysis, correlation coefficients, determination coefficients, and hypothesis tests. The results of the analysis show: Leadership style partially has a significant effect on employee performance with a simple linear regression equation Y = 6,650 + 0.819X1. This is proven by the hypothesis test obtained t count> t table (10,874> 2,001) and is strengthened by a significant value <0.05 (000<0.05). Work discipline partially has a significant effect on employee performance with a simple linear regression equation Y = 2,967 + 0.887X2. This is proven by the hypothesis test which obtained thitung > ttabel (12,431 > 2,001) and is strengthened by a significant value <0.05 (000<0.05). The research results show that leadership style and work discipline simultaneously have a significant effect on employee performance, using the multiple regression equation Y = 3.043 + 0.179X1 + 0.713X2. A correlation value of 0.851 indicates a very strong relationship, and a coefficient of determination of 71.5% indicates that employee performance is influenced by leadership style and work discipline by 71.5%, while other factors contribute to the remaining 28.5%. This is evidenced by the hypothesis test, which obtained a calculated F value > F table (7.580 > 3.15) and is reinforced by a significance value <0.05 (0.00 <0.05). Thus, H0 is rejected and Ha is accepted